The profile and motivation of Chinese students in Costa Rica - Chao Chao, Kuok Wa (2024)
Learning a foreign language such as Chinese foreign language is motivated by various reasons depending on people's interests and motivations. The main objective of this research is to describe the reasons why students in Costa Rica study Chinese as a foreign language. This is an exploratory descriptive quantitative research in which 224 Costa Rican Chinese students participated. A questionnaire applied online during the first and second semester of 2022 was used as a data collection instrument. As main results, it was found that this student population studies Chinese mainly due to the interest in learning a new language, the employment situation, the possibility of communication with people of Chinese origin, scholarship opportunities in China, among others. As conclusions, it is observed that these motivations are in turn of an intrinsic instrumental type.